2021
DOI: 10.1093/neuros/nyab306
|View full text |Cite
|
Sign up to set email alerts
|

Acute Brain Activation Patterns of High- Versus Low-Frequency Stimulation of the Anterior Nucleus of the Thalamus During Deep Brain Stimulation for Epilepsy

Abstract: BACKGROUND Deep brain stimulation (DBS) of the anterior nucleus of the thalamus (ANT) is an increasingly utilized treatment of drug-resistant epilepsy. To date, the effect of high-frequency stimulation (HFS) vs low-frequency stimulation (LFS) in ANT DBS is poorly understood. OBJECTIVE To assess differences in the acute effect of LFS vs HFS in ANT DBS utilizing blood-oxygen-level-dependent (BOLD) functional magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…34,52 A recent study with low-and high-frequency stimulation during resting state fMRI showed that HFS produces activation of DMN and limbic networks of the brain in contrast to LFS. 53 Herrman et al 13 concluded that low response to ANT DBS in their study could have been associated with using a fixed set of electrodes and parameters in all patients without individual adjustment. Open-source research software (Lead-DBS) and commercial software Scientific STIMVIEW) are available that can estimate the field of stimulation, which may improve adjustment of stimulation parameters by targeting brain regions associated with successful treatment (ie, proximity to MTT).…”
Section: Discussionmentioning
confidence: 89%
“…34,52 A recent study with low-and high-frequency stimulation during resting state fMRI showed that HFS produces activation of DMN and limbic networks of the brain in contrast to LFS. 53 Herrman et al 13 concluded that low response to ANT DBS in their study could have been associated with using a fixed set of electrodes and parameters in all patients without individual adjustment. Open-source research software (Lead-DBS) and commercial software Scientific STIMVIEW) are available that can estimate the field of stimulation, which may improve adjustment of stimulation parameters by targeting brain regions associated with successful treatment (ie, proximity to MTT).…”
Section: Discussionmentioning
confidence: 89%
“…ANT stimulation produced activation within several areas of the brain corresponding to the default mode and limbic networks, including the thalamus, bilateral anterior cingulate and posterior cingulate cortex, precuneus, medial prefrontal cortex, amygdala, ventral tegmental area, hippocampus, striatum, and right angular gyrus. Furthermore, Sarica et al and Middlebrooks et al showed that these areas were not activated when the locus of stimulation was moved away from the ANT and when low-frequency stimulation (30 Hz) was used, further highlighting the potential for fMRI in selecting optimal stimulation parameters [58,59].…”
Section: Epilepsymentioning
confidence: 99%
“… 23 A recent study with low- and high-frequency stimulation during resting state fMRI showed that high frequency DBS produced activation of DMN and limbic networks of the brain, in contrast to low-frequency stimulation. 22 Studies of functional connectivity associated with CMT electrode VTAs produced less functional connectivity in regions of DMN, but higher connectivity with sensorimotor, premotor, ACC, ascending reticular activating system (ARAS) and other brain regions ( Table 2 ). 18 , 19 …”
Section: Resultsmentioning
confidence: 99%
“…The common functional connectivity network shared by clinically used DBS targets overlapped regions of the epileptic networks identified by previous studies of regions activated during DBS. 14 , 15 , 22 , 23 This suggests that DBS targets and epilepsy share a common cortico-subcortical network that might be responsible for the antiseizure action of DBS. 21 , 46 , 47 …”
Section: Discussionmentioning
confidence: 99%